Kepemimpinan Formal dalam Lembaga Formal Pendidikan Islam: Eksistensi Kepala Madrasah Sebaga Pemimpin Lembaga Formal - Andi Sulistio; Abd Azis; Nur Efendi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this article is to provide an overview of formal leaders in formal Islamic educational institutions. Formal leaders in formal Islamic education institutions are individuals who give commands or influence subordinates to carry out activities in accordance with established procedures and methods in order to achieve common goals. The method used is library research and content analysis with a qualitative approach. Library research is research carried out by reviewing various journals, books and other relevant references. The research results show that formal leadership in formal Islamic education institutions has a very large role in improving institutional performance in various aspects. There are five dimensions of leadership which include (1) leadership goals, (2) individuals who influence the group (3) individuals who are influenced, (4) interaction processes, and (5) situations where leadership takes place. The most basic types or styles of leadership are authoritarian leadership, democratic leadership and laissez faire leadership. Formal institutions consist of institutions established by the government and non-governmental organizations. Leaders of these institutions are required to have 2 competencies, namely core competencies (soft skills) and technical-knowledge competencies (hard skills). These two competencies are described in levels of proficiency with the lowest level being level 1 and the highest being level 5.